Hoarseness as the Presenting Symptom of Visceral Leishmaniasis with Muco-Cutaneous Lesions: A Case Report - MORTAZAVI, Hossein (Iran J Parasitol, 2015)
Herein, a 28-year-old man with hoarseness, skin and oral lesions is presented. At the time of admission, the patient had an erythematous plaque on his chin near his lower lip and an erythematous-violaceous plaque on his palate near the opening of the pharynx and 20 kg weight lost in last one year. The biopsy of his skin lesions by hematoxylin and eosin staining revealed an infiltration of the dermis by lymphoplasma and histiocytic cells with a loose granuloma formation suggestive of leishmaniasis. Biopsy of mucosal lesions revealed Leishman bodies in dermis. PCR was performed on the specimens of skin, bone marrow, mucosa, and saliva, the results were positive. The pathogenic agent was identified as Leishmania major by the nested PCR. Serologic tests including direct agglutination test (DAT) and indirect immunofluorescence test (IFAT) were positive with high titers of anti-L. infantum antibodies (1:102400 versus 1:800, respectively), indicative of visceral involvement. The patient responded to a combination of miltefosine and meglumine antimoniate (Glucantime®). Visceral involvement due to L. major is rarely reported. To the best of our knowledge, probably hoarseness due to L. major has not been previously reported from Iran.